The impact of E-learning and ICT on English language learning: COVID-19 context - Julio Antonio Álvarez Martínez; Juan Fernando Gómez (Association for Learning Technology, 2023)
Background: E-learning and ICT have developed an innovative way of teaching English. To make sure the learning of this foreign language is effective, educational establishments and universities adjusted their infrastructure and technological devices. Aim: This article aims to present the results from a comprehensive examination of the literature regarding the Effects of E-learning and ICT on English language learning in COVID-19. Methods: The investigators made use of the PRISMA MODEL to determine the 65 articles to be included in the sample selection. A systematic search was performed on databases to select articles on E-learning and ICT related to English language learning. The databases employed for this study were Scielo, Redalyc, Dialnet, cademic Publishing (ACPI), Springer, Scopus, ECLAC, and MINTIC. Results: These technologies experienced an increase in usage during the COVID-19 pandemic. Conclusion: Incorporating e-learning and ICT has made language learning more dynamic. In addition, it demanded training of teachers to manage the tools and resources that they offer.